Madagascar : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
This paper analyzes the basic data, social and demographic indicators of Madagascar. The study outlines the institutional arrangements for the determination and management of the Malagasy franc, and reviews the foreign exchange market developments. The paper assesses the country's international price competitiveness and developments in the export processing zone. This report also provides a Statistical Appendix for the country.